Hemodynamic indices and heart electrical activity among young taekwondo athletes of the Komi Republic during different seasons - Sheveleva, E. S.; Panteleeva, N. I.; Roshchevskaya, I. M. (The Russian Journal of Physical Education and Sport, 2018)
Annotation. Heart electrical activity and the indices of system hemodynamics among 9-12 year-old taekwondo athletes, who live in different climate zones of the Republic of Komi (62° ? 67° ?. ?.), during spring-summer and winter periods in terms of rehabilitation after submaximal physical load was studied. Young taekwondo athletes of subarctic climate zone, in comparison with sportsmen, who live in temperate climate, have less favorable dynamics reaction of cardiovascular system to physical load during winter, than during spring-summer period. Material. Studying young taekwondo athletes` (Syktyvkar and Vorkuta) cardiovascular system reaction to physical load in least and most favorable seasons. Research methods: electrocardiography and blood pressure (BP) and heart rate (HR) monitoring during bicycle ergometry. Result. The highest systolic blood pressure (SBP) and diastolic blood pressure (DBP)indices among taekwondo athletes from Varkuta were revealed during spring-summer period in comparison with the same indices of sportsmen from Syktyvkar. Step-by-step increasing load showed the difference of heart electrical activity indices among young taekwondo athletes, who live in different climatic-geographical zones of the Republic of Komi. Conclusion. It is demonstrated that during spring-summer period hemodynamic reaction to bicycle ergometric functional test was more unfavorable among children of the arctic zone, than among children of the moderate-continental climate and it proves increased tension of compensatory mechanisms of an organism for homeostasis support in terms of extreme natural factors.